Results of testing the energy dispersive Si detector with large working area - Gogolev A. S. Aleksey Sergeevich; Hampai D.; Khusainov A. Kh. Abdurakhman Khusainovich; Zhukov M. P.; Dabagov S. B. Sultan Barasbievich; Potylitsyn A. P. Alexander Petrovich; Liedl A.; Polese C. (2015, 2015)
Title screen